Morphological and Functional Characteristics of the Microenvironment After Pleural Implantation of Biosynthetic Materials - G. A. Demyashkin; T. K. Tokaev; A. S. Bikbaev; M. V. Sinitsyn; T. E. Grigoryev; Yu. D. Zagoskin (Туберкулез и болезни лёгких)
The objective: to study morphological changes in tissues after implantation of a bioresorbable material synthesized on the basis of polylactide (PLA) and polycaprolactone (PCL) in various ratios.Subjects and Methods. Laboratory animals Chinchilla lanigera (n = 12) underwent intrapleural implantation with 2% PLA/PCL 1/1 and 4% PLA/PCL 1/3 materials. Morphometric assessment was carried out in14 and 28 weeks, the animals were withdrawn from the experiment by an anesthetic overdosing.Results. When studying tissues adjacent to the implant regardless of differences in its composition, similar morphological signs were observed. A fibrous capsule formed around the implants, and it was more pronounced in 4% of PLA/PCL 1/3. In the structure of the implants, we noted the growth of loose and dense unformed fibrous connective tissue with blood vessels with a significant replacement of the bioresorbable polymer material (by 2/3). Lymphocytes, plasma cells, single macrophages, and multinucleated cells were predominantly located at the implant/tissue interface. In all studied samples, no necrosis was observed in the implantation bed and surrounding tissue.Conclusion. The data obtained confirm the biosafety of biomaterials and demonstrate the potential for their use in surgical treatment of humans.